Rationalisation of Wages in Forestry - Nair, N. R. (Indian Forester, 1970)
This paper attempts to give, a brief and comprehensive account of the different measures and disciplines available at our disposal, for the rationalisation of wages, such as State Regulations, Work Study, Work Physiology, Job Evaluation and Incentive Schemes. The inter-relationships of these different disciplines in the field of wage fixation is brought out in the concluding part. Brief descriptions of a Job Evaluation and a Work Study-cum-Physiological Study, made with the help of the Forestry Commission of Great Britain, are a1so included.